2019
DOI: 10.1155/2019/1924941
|View full text |Cite
|
Sign up to set email alerts
|

Full Immunization Coverage and Associated Factors among Children Aged 12-23 Months in a Hard-to-Reach Areas of Ethiopia

Abstract: Introduction. Childhood immunization averts 2.5 million annual child deaths globally. However, poor monitoring, possibly due to a lack of locally available data on immunization, might affect full protection of vaccines from Vaccine Preventable Diseases. This study was aimed at bringing data about immunization service coverage and its associated factors from Sekota Zuria district, which is one of the hard-to-reach areas in Amhara Region, Ethiopia. Methods. A community-based cross-sectional study was conducted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
98
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(125 citation statements)
references
References 20 publications
24
98
3
Order By: Relevance
“…As reported by previous studies conducted in different countries [8][9][10][11][12]19], maternal knowledge was found to have significant relationship with immunization status of their children in this study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As reported by previous studies conducted in different countries [8][9][10][11][12]19], maternal knowledge was found to have significant relationship with immunization status of their children in this study.…”
Section: Discussionsupporting
confidence: 81%
“…About 70% of Myanmar people are living in rural area [6,7] and maternal knowledge is found to have significant relationship with immunization status of their children [8][9][10][11][12]. Therefore, this study is conducted to determine the knowledge on routine childhood immunization and the factors associated with it among mothers in rural area of Mon State, Myanmar during 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in addition to closing the gap in educational attainment over the long term, it is necessary to set up an immediate system to inform mothers about the importance of childhood immunization programs. A number of previous studies in different parts of Ethiopia have reported maternal educational level as a significant determinant for immunization coverage [62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…All retained twenty eight studies in this systematic review and meta-analysis conducted in Ethiopia all of them were cross sectional; twenty five of them were conducted from eight regional states and three national survey, a total sample size of 20,048 of (aged 12-23 months) old children included. The minimum sample size was 173 [26] and maximum sample size was 2004 [27] Nin (32.1%) of studies were from Amhara region [28][29][30][31][32][33][34][35][36], six (21.4%) from South Nation Nationality and People's region [18,26,[37][38][39][40], four (14.3%) from Oromia region [41][42][43][44], were three (10.7%) survey nationwide [27,45,46], two (7.1%) from pastoral and semi-pastoral area of the country [25,47], lastly one (3.6%) from Somali state [48] and one (3.6%) from Tigrai regional states [49] All studies were published in peer review journals that fulfills WHO/UNICEF case definition for maternal recall, immunization card and scare were used.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…WHO 2018 reported that That 19.4 million infants are completed DPT3 where 13.5 million didn't received initial dose of vaccine due to lack of access to immunization services, while Ethiopia and other nine countries hold 11.7 million of 19.4 under and unimmunized children which accounts 60% [9] Over 6 million under five children died worldwide in 2013, which several deaths are attributed by VPD. and affordable interventions to decrease under-five mortality there is alarming of VPD like: diarrhea, measles and pneumonia which annually cause 3, 370 00 cases of measles, pneumonia, and diarrhea [5,[10][11][12][13][14][15] There are contributing factors that significantly associate with vaccine coverage in Ethiopia, those are rural residence, employer, female household head, primary and secondary school, antenatal care follow up, delivering health facility, Level of maternal education, good knowledge on immunization, short distance to health facility, having four or more family size can increase vaccine coverage in contrary fear of side effect, low wealth status, being too busy, hearing rumor about vaccination were predictors and barrier of fully vaccination [6,[16][17][18][19] Although private for profit and not for profit health facilities accounts for about 11% of health service coverage in Ethiopia all most all of them are not providing routine immunization if they provide routine immunization with free cost may contribute a lot to the coverage [20] Understanding the extent of vaccine coverage and its associated factors is important for designing strategies that can reduce the burden of vaccine preventable diseases. There is no review and metaanalysis conducted in Ethiopia on immunization coverage among 12-23 month old.…”
mentioning
confidence: 99%